The effectiveness of the thelin model in achieving intermediate second-grade students in history - Al-Janabi, Dr. Abdulbaset Abbas Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to identify the effectiveness of the theline model in the achievement of the second intermediate grade students in the subject of history and by checking the zero hypothesis there is no statistically significant difference between the average scores of students of the experimental group who are studying the subject of the Arab Islamic history using the thelin model and the average score of the control group students Those studying the same subject using the traditional method.For the purpose of achieving the research goal, the researcher prepared the measurement tool as the test consisted of (25) test items of a multiple choice type, its validity and stability were verified, and by statistically processing the data the results showed that the experimental group outperformed the control group in the achievement test, and in light of the research results the researcher recommends By paying attention to the use of modern strategies and models in teaching, including the thelene model in teaching Arabic-Islamic history for the second intermediate grade, and to complement the current study, the researcher suggested several proposals, including: Studying the effectiveness of the thelene model in other subjects and stages of study.